Differential Equations of Processes for the Hydropuls Power Mechanism of Drill Machines; Applied Mechanics and Materials; Vol. 379 : Innovation materials and manufacturing technologies, economic aspects in enterprises - Pashkov E. N. Evgeny Nikolaevich (2013, 2013)
Title screen